2023
DOI: 10.1177/1759720x231157043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical efficiency between intra-articular injection of platelet-rich plasma and hyaluronic acid for osteoarthritis: a meta-analysis of randomized controlled trials

Abstract: Background: Platelet-rich plasma (PRP) and hyaluronic acid (HA) are non-surgical treatments for osteoarthritis (OA), but the comparison of their efficiency is still inconclusive. Objectives: The objectives of this study were to compare the efficacy of PRP and HA in the treatment of OA by meta-analysis and to explore the effects of different injection times and leukocyte concentration on the efficacy of PRP. Design: Meta-analysis and subgroup analysis were conducted. The data were analyzed by Review Manager v5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…In a recent publication, Chen et al (2023) analyzed the effects of PRP versus HA for knee OA based on 30 articles with 2733 patients. The results also confirmed that PRP injection was better than HA injection; in particular, the WOMAC and IKDC scores were better in the PRP group than in the HA group at the last follow-up timepoint 39 . Additionally, in this analysis, Chen et al showed that LP-PRP appeared to be superior to LR-PRP in terms of functional recovery but not in terms of pain relief.…”
Section: Comparisons Of the Therapeutic Effects Of Knee Osteoarthriti...supporting
confidence: 66%
See 1 more Smart Citation
“…In a recent publication, Chen et al (2023) analyzed the effects of PRP versus HA for knee OA based on 30 articles with 2733 patients. The results also confirmed that PRP injection was better than HA injection; in particular, the WOMAC and IKDC scores were better in the PRP group than in the HA group at the last follow-up timepoint 39 . Additionally, in this analysis, Chen et al showed that LP-PRP appeared to be superior to LR-PRP in terms of functional recovery but not in terms of pain relief.…”
Section: Comparisons Of the Therapeutic Effects Of Knee Osteoarthriti...supporting
confidence: 66%
“…Additionally, in this analysis, Chen et al showed that LP-PRP appeared to be superior to LR-PRP in terms of functional recovery but not in terms of pain relief. They also showed that there were no differences between single PRP injections and triple PRP injections 39 . However, in another analysis, Peng et al (2022) compared the effects of LR-PRP and HA and showed that although LR-PRP had no significant pain relief effect, LR-PRP injection demonstrated better overall outcomes than HA injection 40 .…”
Section: Comparisons Of the Therapeutic Effects Of Knee Osteoarthriti...mentioning
confidence: 98%
“…PRP comprises a lot of components that may have various effects on anabolic and catabolic changes in tissues. It has generally shown positive clinical results, including pain relief and improved locomotive function in patients with osteoarthritis [4,8,9]. However, long-term studies are required to clarify its potential to inhibit disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs and corticosteroids are recommended as treatment strategies for this disease, along with patient education and exercise therapy as core treatment strategies [7]. Intra-articular hyaluronic acid injection is also used in outpatient practice; however, PRP has shown a better clinical outcome in a recent study comparing hyaluronic acid [8,9]. To elucidate the superior therapeutic mechanism of PRP, analyzing the biochemical factors contained in PRP may be needed, particularly considering the factors involved in the pathophysiology of osteoarthritis, which is not fully understood, although several studies have been conducted [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to their observation, the use of PRP provides results comparable or even superior to those provided by HA treatments [236]. Also, Chen and colleagues, more recently, published a meta-analysis comparing the results of different literature productions involving more than 2700 patients divided into PRP and HA groups [237]. Its result showed that reported Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain marks were higher for PRP-treated subjects, with comparable safety profiles.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%